The Quality of Innovation Space Management in the Eastern Macro-Region of Russia - Yulia A. Kuznetsova (Регионология, 2022)
Introduction. Increasing requirements for the regions in terms of enhancing innovative development, on the one hand, the complication of innovative activities in the current socio-economic situation, on the other, actualize the task of improving the quality of innovation space management. The purpose of the article is to assess the quality of management of the innovation space of an enlarged territory based on the proposed system of indicators and to formulate recommendations for its improvement.